2012
DOI: 10.1007/s00520-012-1425-8
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient and oral antibiotic management of low-risk febrile neutropenia are effective in children—a systematic review of prospective trials

Abstract: Based on the combination of results from all prospective studies to date, outpatient and oral antibiotic management of low-risk FN are effective in children and should be incorporated into clinical care where feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 46 publications
0
40
0
1
Order By: Relevance
“…[4,5] Evidence shows that some pediatric patients with cancer who develop FN could be treated as outpatients or have an early discharge or even be treated as an outpatient. [6][7][8] Adoption of these practices would require institution specific systems to be in place for risk stratification and outpatient monitoring, with consideration for patient travel and social circumstances. [9] Evaluation of the impact of FN on health care utilization in the United States (US) could lead to improved insight into both hospital-and patient-level factors that impact length of stay.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Evidence shows that some pediatric patients with cancer who develop FN could be treated as outpatients or have an early discharge or even be treated as an outpatient. [6][7][8] Adoption of these practices would require institution specific systems to be in place for risk stratification and outpatient monitoring, with consideration for patient travel and social circumstances. [9] Evaluation of the impact of FN on health care utilization in the United States (US) could lead to improved insight into both hospital-and patient-level factors that impact length of stay.…”
Section: Introductionmentioning
confidence: 99%
“…. [20][21][22][23][24]. Dans notre étude, nous avons choisi de proposer un relais de l'antibiothérapie par voie orale à H72, malgré la persistance de la neutropénie, en l'absence de fièvre et de documentation bactériologique chez un enfant en bon état général compliant à la prise orale des antibiotiques et pour lequel la PCT était infé-rieure à 0,12 mg/L au moment de la prise en charge de la NF.…”
Section: Discussionunclassified
“…16 This recommendation is based on a review of 16 mostly small single-center prospective trials of pediatric low-risk febrile neutropenia that found no increase in treatment failure and when outpatient treatment was compared with inpatient management and found no infection-related deaths in patients that were treated as outpatients. 37 In addition, research comparing parental and oral antibiotic therapy in low-risk febrile neutropenia patients found no difference in treatment failure and no infection-related deaths. 37 Oral antibiotics used in these studies were either fluoroquinolone monotherapy, fluoroquinonlone and amoxicillin-clavulanate, or cefixime monotherapy.…”
Section: Hematopoietic Growth Factorsmentioning
confidence: 99%
“…37 In addition, research comparing parental and oral antibiotic therapy in low-risk febrile neutropenia patients found no difference in treatment failure and no infection-related deaths. 37 Oral antibiotics used in these studies were either fluoroquinolone monotherapy, fluoroquinonlone and amoxicillin-clavulanate, or cefixime monotherapy. 37 The research suggests that there may be certain subpopulations of low risk febrile neutropenia oncology patients in whom early discharge off antibiotics is safe, but ongoing research needs to be performed.…”
Section: Hematopoietic Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation